The U.S. Mineral Property Valuation Patchwork of Regulations and Standards (b596e322-36dd-40ba-820a-fc3646322652) - Trevor R. Ellis (Canadian Institute of Mining, Metallurgy and Petroleum, 2003)
"The valuation of mineral properties in the U.S. is only partially regulated. The regulations which have jurisdiction or impact appear to have such mainly as a consequence of unintended fallout, since the regulations were designed for other purposes. Court case history can also be important. The combined results are a mixture of bad and good, with important lessons to be learned.Since 1981, the Securities and Exchange Commission has prohibited U.S. listed companies from reporting quantitative estimates of mineralization and the value of mineralization, other than proven and probable reserves. This results in the minerals appraiser (valuator) working with a shortage of data in his everyday work, both on the subject property and in sales analysis.Between 1989 and 1995, all 50 states and essentially all Federal agencies adopted the Uniform Standards of Professional Appraisal Practice (USPAP) for real property appraisals (valuations). The major national appraisal societies also require their members to abide by USPAP. A significant portion of minerals appraisals must now follow these standards. This paper will discuss the content of USPAP. It provides a very good framework for the valuation of a minerals property or a mine, both as real property and as a business. However, the credentialing standards for real property appraisers are now prohibitive for minerals appraisers."